PENGEMBANGAN SISTEM INFORMASI E-LEARNING MENGGUNAKAN METODE WATERFALL (STUDI KASUS: SMA NEGERI 1 MEGAMENDUNG JAWA BARAT) - Siti Fatimah (2021)
The e-learning information system is one of the media that can help the process of teaching and learning activities. The process of teaching and learning fluency can be relied on by the quality of its information system. The functionality and quality of the system can be said to be successful if users can obtain information that suits their needs. SMA Negeri 1 Megamendung West Java has just implemented an e-learning information system to assist teaching and learning activities. There are still several ways of implementing e-learning teaching materials that are not available and there are no online assignments. Therefore, this study aims to provide recommendations for additional features in the e-learning of SMA Negeri 1 Megamendung, West Java. This research was conducted using the PIECES method to analyze websites and using the Waterfall method for software development. The author provides several recommendations for adding features to e-learning which are expected to be a system repair solution and improve the quality of e-learning at SMA Negeri 1 Megamendung.